PROBLEMS OF DEVELOPMENT OF ORAL SPEECH AMONG STUDENTS OF TECHNICAL UNIVERSITIES OF THE REPUBLIC OF UZBEKISTAN - Zokirova Zulfiya Tursunovna (Western European Studies, 2024)
The article examines the current problems related to the development of oral speech of students of technical universities in the Republic of Uzbekistan. The authors analyze the factors influencing the formation and improvement of students' oral communication skills, the peculiarities of education and upbringing in technical universities, and also propose effective methods and approaches to the development of oral speech. The research is based on the analysis of academic research, pedagogical experience and practical observations. The results of the work can be useful both for teachers working in technical universities and for students seeking to develop their communication skills in the professional field.
Keywords: communication; Oral speech; students of technical universities; educational methods